Polarizing plate and optical display device including the same
By using hydrophobic polyvinyl alcohol resin and a polarizer that controls surface roughness, combined with the metal-containing powder paste deposited on the polarizer, the metal ion penetration and static problems are solved, and the efficient performance of the polarizer in the liquid crystal display is achieved. and static removal.
Patent Information
- Application Number
- CN202110896390.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-08-10
- Filing Date
- 2021-08-05
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2041-08-05
AI Technical Summary
In liquid crystal displays, when a paste containing metal powder is deposited on the polarizing plate under high temperature and high humidity conditions, metal ions are prone to penetrate between the polarizer and the protective film, resulting in a decrease in polarization function and luminous efficiency, and at the same time, it is difficult to have static electricity problems. solve.
Hydrophobic polyvinyl alcohol resin is used as the polarizer material, with a surface roughness of 10 nm or less. By depositing a paste containing metal powder in the thickness direction of the polarizer plate, it is placed at 60°C and 95% RH for 240 hours. , minimize metal ion permeability length to 400μm or less.
It effectively reduces the penetration of metal ions between the polarizer and the protective film, prevents the influence of static electricity, and removes static electricity, maintains the polarization function and luminous efficiency of the polarizer.
Smart Images

Figure CN114077003B_ABST
Abstract
Description
[0001] Citations of Related Applications
[0002] This application claims the benefit of Korean Patent Application No. 10-2020-0099645 filed on August 10, 2020, in the Korean Intellectual Property Office, the disclosure of which is incorporated herein by reference in its entirety. Technical Field
[0003] The present invention relates to a polarizing plate and an optical display device including the same. More particularly, the present invention relates to a polarizing plate that can minimize the penetration of metal ions between a polarizer and a protective film when a paste containing metal powder is deposited on the polarizing plate in a thickness direction and placed at high temperature and / or under high temperature / high humidity conditions, and to an optical display device including the polarizing plate. Background Art
[0004] The liquid crystal display includes a polarizing plate bonded to both sides of the liquid crystal panel by an adhesive layer (adhesive layer) such as a pressure-sensitive adhesive (PSA) layer. Generally, the liquid crystal display adopts an add-on type structure, in which a touch panel or a touch sensor independent of the liquid crystal panel is placed on one side or both sides of the liquid crystal panel. However, the add-on type has the problem of increasing the thickness of the liquid crystal display. In order to solve this problem, an in-cell type liquid crystal display having a touch panel or a touch sensor inside the liquid crystal panel is used.
[0005] The in-cell liquid crystal display includes a touch panel or a touch sensor inside a liquid crystal panel. The in-cell liquid crystal display is manufactured by bonding a polarizing plate to which a release film is bonded via an adhesive layer to both sides of a liquid crystal panel through a pressure-sensitive adhesive, and then removing the release film to which the adhesive layer is attached from the polarizing plate. The release film to which the adhesive layer is attached (e.g., a polyethylene terephthalate (PET) film) is a processing film that protects the polarizing plate from foreign matter and is removed from the polarizing plate after the polarizing plate is bonded to both sides of the liquid crystal panel.
[0006] However, static electricity may be generated in the process of removing the release film from the polarizing plate. In addition, static electricity may be applied to the liquid crystal display during the process of manufacturing the liquid crystal display. The static electricity may affect the touch panel or touch sensor inside the liquid crystal panel.
[0007] In order to prevent static electricity from damaging the liquid crystal panel, static electricity must be dissipated. To this end, the polarizing plate is subjected to ESD treatment by coating a paste containing metal powder, such as a paste containing silver powder, in the thickness direction of the polarizing plate. Here, the silver powder in the paste produces silver ions (Ag+) by ionization when in contact with heat, moisture or acid. The silver ions penetrate between the polarizer and the protective film, between the protective film and the pressure-sensitive adhesive layer, or between the pressure-sensitive adhesive layer and the liquid crystal panel. The infiltrated silver ions grow into silver crystals, which will reduce the luminous efficiency of the light emitted by the liquid crystal panel. In particular, the silver ions or silver crystals produced therefrom that penetrate between the polarizer and the protective film will affect the light passing through the polarizer, thereby affecting the polarizing function of the polarizing plate. Therefore, it is necessary to develop a polarizing plate that minimizes the penetration of silver ions between the polarizer and the protective film while being able to remove static electricity from the polarizing plate.
[0008] The background art of the present invention is disclosed in Korean Patent Publication No. 10-2013-0078606 and the like. Summary of the invention
[0009] One aspect of the present invention is to provide a polarizing plate that minimizes penetration of metal ions between a polarizer and a protective film when a paste containing metal powder is deposited on the polarizing plate in a thickness direction and left at high temperature and / or under high temperature / high humidity conditions.
[0010] One aspect of the present invention relates to a polarizing plate.
[0011] Aspect 1. A polarizing plate includes a polarizer and a protective film stacked on at least one surface of the polarizer, wherein the polarizer includes a hydrophobic polyvinyl alcohol resin and has a surface roughness (Ra) of 10 nm or less on its surface facing the protective film, and when a paste containing a metal powder is deposited on its surface in a thickness direction of the polarizing plate and placed at 60°C and 95% relative humidity (RH) for 240 hours, the maximum metal ion penetration length of the polarizing plate between the polarizer and the protective film is 400 μm or less.
[0012] Aspect 2. In aspect 1, the polarizer may have a surface roughness (Rz) of 0 nm to 80 nm on its surface facing the protective film and a surface roughness (Rq) of 0 nm to 20 nm on its surface facing the protective film.
[0013] Aspect 3. In any one of aspects 1 and 2, the polarizer may have a difference of 5 nm or less in surface roughness (Ra) between opposite surfaces thereof.
[0014] Aspect 4. In any one of aspects 1 to 3, the hydrophobic polyvinyl alcohol resin may contain unsubstituted C1 to C 20 The hydrocarbon group serves as a hydrophobic functional group.
[0015] Aspect 5. In any one of aspects 1 to 4, the hydrophobic polyvinyl alcohol resin may include a copolymer of a monomer mixture including at least one vinyl ester monomer and a monomer providing a hydrophobic functional group.
[0016] Aspect 6. In aspect 5, the monomer providing the hydrophobic functional group may include a monomer having C1 to C 20 A monomer having a hydrocarbon repeating unit.
[0017] Aspect 7. In any one of aspects 1 to 6, the thickness of the polarizer may be 12 μm or less.
[0018] Aspect 8. In any one of Aspects 1 to 7, the protective film may include at least one selected from cellulose ester resin, cyclic polyolefin resin, polycarbonate resin, polyester resin, polyether sulfone resin, polysulfone resin, polyamide resin, polyimide resin, non-cyclic polyolefin resin, polyacrylate resin, polyvinyl alcohol resin, polyvinyl chloride resin, polyvinylidene chloride resin and acrylic resin.
[0019] Aspect 9. In any one of aspects 1 to 8, the polarizer is bonded to the protective film via an adhesive layer, the adhesive layer having a thickness of 0.01 μm to 10 μm.
[0020] Another aspect of the present invention relates to an optical display device.
[0021] An optical display device includes the polarizing plate according to the present invention.
[0022] The present invention provides a polarizing plate capable of minimizing the penetration of metal ions between a polarizer and a protective film when a paste containing a metal powder is deposited on the polarizing plate in a thickness direction and left at high temperature and / or under high temperature / high humidity conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is a cross-sectional view of a polarizing plate according to one embodiment of the present invention, in which a metal paste is deposited thereon in a thickness direction of the polarizing plate.
[0024] Figure 2 1 is a scanning electron micrograph (SEM) and an enlarged view of a cross section of a polarizing plate according to an embodiment, in which a metal paste is deposited thereon in a thickness direction of the polarizing plate.
[0025] Figure 3 is a cross-sectional view of an optical display device according to one embodiment of the present invention.
[0026] Figure 4The graph shows the infiltration length of metal ions in the polarizing plates of Comparative Example 1 and Example 1. DETAILED DESCRIPTION
[0027] The embodiments of the present invention will be described in detail with reference to the accompanying drawings to provide a thorough understanding of the present invention to those skilled in the art. It should be understood that the present invention can be embodied in different ways and is not limited to the following embodiments.
[0028] Herein, the “maximum metal ion penetration length” in the polarizing plate refers to the maximum value of the metal ion penetration length between the polarizer and the protective film of the polarizing plate when a paste containing metal powder is deposited on the surface of the polarizing plate in the thickness direction and placed at 60°C and 95% RH for 240 hours.
[0029] In one embodiment, the metal ions may be derived from a paste containing metal powder. Upon contact with heat, moisture or acid, the paste containing metal powder is ionized to generate metal cations. For example, a paste containing silver powder will generate silver ions (Ag + ).
[0030] The infiltrated metal cations grow into metal crystals. For example, a paste containing silver powder will produce silver cations. The metal ion penetration length can be measured using an optical microscope (ML61L, Olympus Co., Ltd.).
[0031] The metal powder-containing paste includes 40 to 90 wt % of metal powder having an average particle size (D50) of 1 to 10 μm, 5 to 30 wt % of a binder, and the balance of solvent (eg, 3 to 60 wt % or 3 to 55 wt %).
[0032] The metal powder may include at least one selected from silver (Ag) powder and platinum (Pt) powder. The metal powder may have a spherical, flaky or needle-like shape. The binder may include cellulose acetate propionate, cellulose acetate butyrate or a mixture thereof. The solvent may include at least one selected from water, ethanol, butanol and propylene glycol methyl acetate (PGMEA).
[0033] The metal powder-containing paste may have a viscosity of 50,000 cP to 300,000 cP at a temperature of 20° C. to 25° C. The viscosity may be measured using a viscometer (DV-E, Brookfield Co., Ltd.).
[0034] For example, a syringe may be filled with the metal powder-containing paste and then the metal powder-containing paste may be injected toward the surface of the polarizing plate in a thickness direction thereof to deposit the metal powder-containing paste, but is not limited thereto.
[0035] After the metal powder-containing paste is deposited on the polarizing plate in the thickness direction thereof, the metal powder-containing paste may remain in the optical display device employing the polarizing plate or may be removed therefrom.
[0036] Herein, the surface roughness Ra, Rz, and Rq of the polarizer were measured in a non-contact mode of an atomic force microscope (AFM).
[0037] As used herein to express a specific numerical range, the expression "X to Y" means "greater than or equal to X and less than or equal to Y (X≤ and ≤Y)."
[0038] As used herein, the term "(meth)acryl" refers to acryl and / or methacryl.
[0039] Next, we will refer to Figure 1 A polarizing plate according to one embodiment of the present invention is described.
[0040] The polarizing plate according to the present invention comprises a polarizer and a protective film stacked on at least one surface of the polarizer, wherein the polarizer comprises a hydrophobic polyvinyl alcohol resin and has a surface roughness (Ra) of 10 nm or less on a surface thereof facing the protective film. Therefore, the maximum metal ion penetration length of the polarizing plate according to the present invention is 400 μm or less and there is no problem of bubbles being generated when the polarizer is bonded to the protective film.
[0041] If the surface roughness Ra on the surface of the polarizer facing the protective film is 10 nm or less and the polarizer contains a hydrophilic polyvinyl alcohol resin, the maximum metal ion penetration length of the polarizing plate can exceed 400 μm. If the polarizer contains a hydrophobic polyvinyl alcohol resin and the surface roughness Ra on the surface of the polarizer facing the protective film exceeds 10 nm, the maximum metal ion penetration length of the polarizing plate can exceed 400 μm.
[0042] See also Figure 1 The polarizing plate includes a polarizer 10 , a first protective film 20 and a second protective film 30 .
[0043] The polarizing plate may further include a release film ( Figure 1 In order to apply the polarizing plate to an optical display device, the pressure-sensitive adhesive layer (not shown) is used to protect the polarizing plate. Figure 1 (not shown) the polarizing plate is adhered to the optical display panel, and the release film to which the adhesive layer is attached is peeled off from the polarizing plate.
[0044] However, static electricity may be generated in the process of removing the release film from the polarizing plate. In addition, static electricity may be generated in the process of manufacturing the optical display device. Static electricity may affect the touch panel or touch sensor inside the liquid crystal panel. In order to remove static electricity outside, a paste 40 containing metal powder is deposited on the surface of the polarizing plate in the thickness direction thereof.
[0045] According to the present invention, a maximum metal ion penetration length of 400 μm or less is set to provide an effect of removing static electricity when a release film having an adhesive layer attached to one surface is removed from the polarizing plate after being stacked on the polarizing plate without affecting the polarizing function and luminous efficiency of the polarizing plate. Specifically, the maximum metal ion penetration length may be greater than 0 μm to 400 μm, more specifically 0 μm to 200 μm. For example, the maximum metal ion penetration length can be 0μm, 10μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm, 150μm, 160μm, 170μm, 180μm, 190μm, 200μm, 210μm, 220μm, 230μm, 240μm, 250μm, 260μm, 270μm, 280μm, 290μm, 300μm, 310μm, 320μm, 330μm, 340μm, 350μm, 360μm, 370μm, 380μm, 390μm or 400μm.
[0046] In one embodiment, the surface roughness (Ra) of the polarizer on the surface facing the protective film is greater than 1.0nm to 10nm, preferably 1.1nm to 10nm. Within this range, the polarizing plate can have a maximum metal ion penetration length of 400μm or less, and allows the polarizer to be easily manufactured without affecting the polarizing function. For example, the surface roughness (Ra) of the polarizer on the surface facing the protective film is 1.1nm, 1.2nm, 1.3nm, 1.4nm, 1.5nm, 1.6nm, 1.7nm, 1.8nm, 1.9nm, 2nm, 2.5nm, 3nm, 3.5nm, 4nm, 4.5nm, 5nm, 5.5nm, 6nm, 6.5nm, 7nm, 7.5nm, 8nm, 8.5nm, 9nm, 9.5nm or 10nm.
[0047] Figure 1 is a cross-sectional view of a polarizing plate according to one embodiment of the present invention, in which a metal paste is deposited thereon in a thickness direction of the polarizing plate.
[0048] See also Figure 1(A), when the paste containing metal powder is deposited on the surface of the polarizing plate in the thickness direction thereof and the polarizing plate is attached to a substrate 50 (such as a glass plate, etc.), the paste containing metal powder forms a coating, thereby providing an ESD effect. Metal ions derived from the paste containing metal powder can penetrate into the gap between the polarizer 10 and the first protective film 20 and the gap between the polarizer 10 and the second protective film 30.
[0049] Figure 1 (B) is Figure 1 (A) is an exploded perspective view of the polarizing plate shown in FIG. Figure 1 (B), metal ions derived from the paste containing the metal powder may penetrate into the gap between the polarizer 10 and the first protective film 20 and the gap between the polarizer 10 and the second protective film 30. Therefore, the metal ion penetration length 60 may be measured.
[0050] Figure 2 are a scanning electron micrograph (SEM) and an enlarged view of a cross section of a polarizing plate according to an embodiment, in which a metal paste is deposited thereon in a thickness direction of the polarizing plate.
[0051] See also Figure 2 , the polarizing plate includes a triacetyl cellulose (TAC) film, a polarizer (PVA) and a hard-coated triacetyl cellulose (HC TAC) film stacked on a glass plate via a pressure-sensitive adhesive (PSA), a silver (Ag) paste is deposited thereon in the thickness direction of the polarizing plate, and metal ions are impregnated into the polarizing plate, as shown in ① and ②.
[0052] The maximum metal ion permeation length according to the present invention can be achieved by a polarizing plate containing a hydrophobic polyvinyl alcohol resin and including a polarizer having a surface roughness (Ra) of 10 nm or less on a surface thereof facing the protective film.
[0053] The “hydrophobic polyvinyl alcohol resin” refers to a polyvinyl alcohol resin containing only hydrophobic functional groups or a polyvinyl alcohol resin in which the amount of the hydrophobic functional groups is greater than the amount of the hydrophilic functional groups among the plurality of functional groups in the polyvinyl alcohol resin.
[0054] Furthermore, the “hydrophilic polyvinyl alcohol resin” refers to a polyvinyl alcohol resin containing only hydrophilic functional groups or a polyvinyl alcohol resin in which the amount of hydrophilic functional groups is greater than the amount of hydrophobic functional groups among multiple functional groups in the polyvinyl alcohol resin.
[0055] In one embodiment, the "hydrophobic functional group" refers to an unsubstituted C1 to C 20 , preferably C1 to C 10 , more preferably C2 to C5 hydrocarbon groups. In one embodiment, the "hydrophilic functional group" refers to a functional group other than a hydrophobic functional group.
[0056] The polyvinyl alcohol resin film contains a hydrophobic functional group. The polyvinyl alcohol film containing a hydrophobic functional group is manufactured by the following process, whereby the polarizer can easily achieve a surface roughness (Ra) of 10 nm or less on its surface facing the protective film.
[0057] The hydrophobic functional group may be present on at least one of the main chain and the side chain of the polyvinyl alcohol resin constituting the polyvinyl alcohol film. The "main chain" refers to the part forming the polyvinyl alcohol resin skeleton, and the "side chain" refers to the part connected to the skeleton. Preferably, the hydrophobic functional group is present on the main chain of the polyvinyl alcohol resin.
[0058] The polyvinyl alcohol resin film may further contain a hydrophilic functional group (eg, -OH). The hydrophilic functional group promotes dyeing.
[0059] In one embodiment, the polyvinyl alcohol resin film may include a copolymer of a monomer mixture including a monomer providing a hydrophobic functional group and at least one type of vinyl ester monomer, such as vinyl acetate, vinyl formate, vinyl propionate, vinyl butyrate, vinyl pivalate (vinyl pivalate, trimethylacetic acid vinyl ester) and isopropenyl acetate. Preferably, the vinyl ester monomer may include vinyl acetate. The monomer providing a hydrophobic functional group may include a monomer having a C1 to C 20 , preferably C1 to C 10 , more preferably monomers of C2 to C5 hydrocarbon (e.g., alkylene) repeating units, the hydrocarbon repeating units including ethylene, propylene, butylene, pentylene, hexylene, heptylene, octylene, nonylene and decylene repeating units.
[0060] The softening point of the polyvinyl alcohol resin film may be 65°C to 80°C, for example 65°C to 71°C, specifically 66°C to 69°C. Within this range, the polyvinyl alcohol resin film does not break or melt during stretching, and allows easy manufacture of the polarizer according to the present invention. For example, the softening point of the polyvinyl alcohol resin film may be 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C or 80°C.
[0061] Measured in the machine direction, the tensile strength of the polyvinyl alcohol resin film can be 80MPa to 120MPa, preferably 90MPa to 110MPa. Within this range, the polyvinyl alcohol resin film will not break or melt during stretching, the polarization degree can be increased by the effective alignment of the polyvinyl alcohol molecular chains, and the polarizer according to the present invention can be easily manufactured. The tensile strength of the polyvinyl alcohol resin film can be measured at 25°C using a universal testing machine (UTM) according to ASTM D882. For example, the tensile strength of the polyvinyl alcohol resin film measured in the machine direction can be 80 MPa, 81 MPa, 82 MPa, 83 MPa, 84 MPa, 85 MPa, 86 MPa, 87 MPa, 88 MPa, 89 MPa, 90 MPa, 91 MPa, 92 MPa, 93 MPa, 94 MPa, 95 MPa, 96 MPa, 97 MPa, 98 MPa, 99 MPa, 100 MPa, 101 MPa, 102 MPa, 103 MPa, 104 MPa, 105 MPa, 106 MPa, 107 MPa, 108 MPa, 109 MPa, 110 MPa, 111 MPa, 112 MPa, 113 MPa, 114 MPa, 115 MPa, 116 MPa, 117 MPa, 118 MPa, 119 MPa, or 120 MPa.
[0062] The thickness of the polyvinyl alcohol resin film may be 50 μm or less, for example, greater than 0 μm to 50 μm or less, specifically 10 μm to 50 μm. Within this range, the polyvinyl alcohol resin film will not break or melt during stretching. For example, the thickness of the polyvinyl alcohol resin film may be 0.01 μm, 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm m, 23μm, 24μm, 25μm, 26μm, 27μm, 28μm, 29μm, 30μm, 31μm, 32μm, 33μm, 34μm, 35μm, 36μm , 37μm, 38μm, 39μm, 40μm, 41μm, 42μm, 43μm, 44μm, 45μm, 46μm, 47μm, 48μm, 49μm or 50μm.
[0063] The polyvinyl alcohol resin film may be a VF-TS#2000PVA film (Kuraray Co., Ltd.).
[0064] The polarizer is manufactured by processing a polyvinyl alcohol film in the order of dyeing, cross-linking, and stretching processes. Therefore, the polarizer can easily achieve a surface roughness (Ra) of 10 nm or less on its surface facing the protective film.
[0065] The dyeing process includes treating the polyvinyl alcohol film in a dye bath containing a dichroic material. In the dyeing process, the polyvinyl alcohol film is immersed in the dye bath containing the dichroic material. The dye bath containing the dichroic material is filled with a dyeing aqueous solution including the dichroic material and a boron compound. Since the dyeing solution contains both the dichroic material and the boron compound, the dyed polyvinyl alcohol film can be prevented from breaking during the stretching process under the following conditions.
[0066] The dichroic material may be an iodine compound and may include at least one selected from potassium iodide, hydrogen iodide, lithium iodide, sodium iodide, zinc iodide, aluminum iodide, lead iodide, and copper iodide. The dichroic material is preferably present in an amount of 0.5 mol / ml to 10 mol / ml in the dye bath (preferably in the dye solution), more preferably 0.5 mol / ml to 5 mol / ml. Within this range, the polyvinyl alcohol film can be uniformly dyed. For example, the dichroic material may be present in the dye bath, preferably in the dye liquor, in an amount of 0.5 mol / ml, 0.6 mol / ml, 0.7 mol / ml, 0.8 mol / ml, 0.9 mol / ml, 1 mol / ml, 1.5 mol / ml, 2 mol / ml, 2.5 mol / ml, 3 mol / ml, 3.5 mol / ml, 4 mol / ml, 4.5 mol / ml, 5 mol / ml, 5.5 mol / ml, 6 mol / ml, 6.5 mol / ml, 7 mol / ml, 7.5 mol / ml, 8 mol / ml, 8.5 mol / ml, 9 mol / ml, 9.5 mol / ml or 10 mol / ml.
[0067] The boron compound can help prevent the polyvinyl alcohol film from breaking or melting when the polyvinyl alcohol film is stretched. Even if the polyvinyl alcohol film is stretched at a high elongation and high temperature after the dyeing process, the boron compound can help prevent the polyvinyl alcohol film from melting or breaking.
[0068] The boron compound may include at least one selected from boric acid and borax. The amount of the boron compound in the dye bath (preferably in the dye liquor) is preferably 0.1wt% to 5wt%, more preferably 0.3wt% to 3wt%. Within this range, the polyvinyl alcohol film can be dyed and can show high reliability without melting and breaking. For example, the amount of the boron compound in the dye bath (preferably in the dye liquor) can be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt%.
[0069] The temperature of the dyeing solution may be 20° C. to 50° C., specifically 25° C. to 40° C. In the dyeing process, the polyvinyl alcohol film may be immersed in the dyeing bath for 30 seconds to 120 seconds, specifically 40 seconds to 80 seconds.
[0070] For example, the temperature of the dyeing solution may be 20° C., 21° C., 22° C., 23° C., 24° C., 25° C., 26° C., 27° C., 28° C., 29° C., 30° C., 31° C., 32° C., 33° C., 34° C., 35° C., 36° C., 37° C., 38° C., 39° C., 40° C., 41° C., 42° C., 43° C., 44° C., 45° C., 46° C., 47° C., 48° C., 49° C., or 50° C. For example, in the dyeing process, the polyvinyl alcohol film is immersed in the dyeing bath for 30 seconds, 35 seconds, 40 seconds, 45 seconds, 50 seconds, 55 seconds, 60 seconds, 65 seconds, 70 seconds, 75 seconds, 80 seconds, 85 seconds, 90 seconds, 95 seconds, 100 seconds, 105 seconds, 110 seconds, 115 seconds, or 120 seconds.
[0071] A cross-linking process is performed to allow the dichroic material to be strongly adsorbed to the polyvinyl alcohol film that has undergone the dyeing process. A cross-linking solution used in the cross-linking process includes a boron compound. The boron compound can help achieve strong adsorption of the dichroic material while improving reliability even when the polarizer is placed under thermal shock.
[0072] The boron compound may include at least one selected from boric acid and borax. The amount of the boron compound in the cross-linking bath (preferably in the cross-linking solution) is preferably 0.5wt% to 10wt%, more preferably 1wt% to 5wt%. Within this range, the polyvinyl alcohol film can be stretched and can show high reliability, while achieving the surface roughness of the polarizer according to the present invention under the conditions of not melting and breaking. For example, the amount of the boron compound in the cross-linking bath (preferably in the cross-linking solution) can be 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt% or 10wt%.
[0073] The temperature of the cross-linking bath may be 20 to 50° C., specifically 25 to 40° C. In the cross-linking process, the polyvinyl alcohol film may be immersed in the cross-linking bath for 30 to 120 seconds, specifically 30 to 80 seconds.
[0074] For example, the cross-linking bath may be set to 20° C., 21° C., 22° C., 23° C., 24° C., 25° C., 26° C., 27° C., 28° C., 29° C., 30° C., 31° C., 32° C., 33° C., 34° C., 35° C., 36° C., 37° C., 38° C., 39° C., 40° C., 41° C., 42° C., 43° C., 44° C., 45° C., 46° C., 47° C., 48° C., 49° C., or 50° C. For example, the cross-linking process may be performed by immersing the polyvinyl alcohol film in the cross-linking bath for 30 seconds, 35 seconds, 40 seconds, 45 seconds, 50 seconds, 55 seconds, 60 seconds, 65 seconds, 70 seconds, 75 seconds, 80 seconds, 85 seconds, 90 seconds, 95 seconds, 100 seconds, 105 seconds, 110 seconds, 115 seconds, or 120 seconds.
[0075] The stretching process includes stretching the dyed polyvinyl alcohol film at a predetermined elongation and at a temperature of 50°C or higher (e.g., 50°C to 70°C). Typically, when the polyvinyl alcohol film is stretched at a temperature higher than the elongation and the stretching temperature, the polarizer cannot be manufactured due to the melting and / or breaking of the polyvinyl alcohol film. Within the above range, the polarizer may have a surface roughness according to the present invention. For example, in the stretching process, the dyed polyvinyl alcohol film may be stretched at a predetermined elongation and at 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C or 70°C.
[0076] In the process of manufacturing the polarizer according to the present invention, the polyvinyl alcohol film is stretched to a total elongation of 5.0 times or more of its initial length, for example, 5.0 to 7 times, preferably 5.4 to 6.5 times, through a dyeing process, a cross-linking process, and a stretching process. Here, "total elongation" is a value obtained by multiplying the elongation of the process. For example, in the process of manufacturing the polarizer, the polyvinyl alcohol film can be stretched to a total elongation of 5 times, 5.1 times, 5.2 times, 5.3 times, 5.4 times, 5.5 times, 5.6 times, 5.7 times, 5.8 times, 5.9 times, 6 times, 6.1 times, 6.2 times, 6.3 times, 6.4 times, 6.5 times, 6.6 times, 6.7 times, 6.8 times, 6.9 times or 7.0 times.
[0077] The stretching process may be achieved by wet stretching or dry stretching. Preferably, the stretching process includes wet stretching to apply the boron compound to the polyvinyl alcohol film. The wet stretching includes uniaxially stretching the polyvinyl alcohol film in a machine direction in an aqueous solution containing the boron compound.
[0078] The boron compound may include at least one selected from boric acid and borax, preferably boric acid. The boron compound is preferably present in an amount of 0.5wt% to less than 3.5wt%, preferably 1wt% to 3.4wt% in the stretching bath (preferably the stretching solution). Within this range, the polarizer can have a surface roughness according to the present invention and can achieve high reliability without melting and breaking during the stretching process. For example, the boron compound may be present in the stretching bath (preferably in the stretching solution) in an amount of 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt%, 1 wt%, 1.1 wt%, 1.2 wt%, 1.3 wt%, 1.4 wt%, 1.5 wt%, 1.6 wt%, 1.7 wt%, 1.8 wt%, 1.9 wt%, 2 wt%, 2.1 wt%, 2.2 wt%, 2.3 wt%, 2.4 wt%, 2.5 wt%, 2.6 wt%, 2.7 wt%, 2.8 wt%, 2.9 wt%, 3 wt%, 3.1 wt%, 3.2 wt%, 3.3 wt% or 3.4 wt%.
[0079] In one embodiment, the polarizer may contain 2.0wt% to 4.0wt%, specifically 2.5wt% to 3.5wt% of the boron compound. Within this range, the polarizer may have a surface roughness according to the present invention. For example, in the polarizer, the boron compound may be present in an amount of 2wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.7wt%, 2.8wt%, 2.9wt%, 3wt%, 3.1wt%, 3.2wt%, 3.3wt%, 3.4wt%, 3.5wt%, 3.6wt%, 3.7wt%, 3.8wt%, 3.9wt% or 4wt%.
[0080] Prior to the dyeing process, the polyvinyl alcohol film may be subjected to at least one of a washing process and a swelling process.
[0081] The washing process is a process of washing the polyvinyl alcohol film using water to remove impurities from the polyvinyl alcohol film.
[0082] In the swelling process, the polyvinyl alcohol film is immersed in a swelling bath at a predetermined temperature to promote dyeing and stretching of the dichroic material. The swelling process includes a process of swelling the polyvinyl alcohol film at 15° C. to 35° C. (preferably 20° C. to 30° C.) for 30 seconds to 50 seconds. Within this range, the polarizer according to the present invention can be effectively implemented.
[0083] In the process of manufacturing the polarizer according to the present invention, the polyvinyl alcohol film is stretched to a total elongation of 5.0 times or more of its initial length, for example, 5.0 to 7 times, preferably 5.4 to 6.5 times, through a washing process, a swelling process, a dyeing process, a cross-linking process, and a stretching process. For example, in the manufacture of the polarizer, the polyvinyl alcohol film can be stretched to a total elongation of 5 times, 5.1 times, 5.2 times, 5.3 times, 5.4 times, 5.5 times, 5.6 times, 5.7 times, 5.8 times, 5.9 times, 6 times, 6.1 times, 6.2 times, 6.3 times, 6.4 times, 6.5 times, 6.6 times, 6.7 times, 6.8 times, 6.9 times or 7.0 times.
[0084] After the stretching process, the polyvinyl alcohol film may be further subjected to a color-correcting process.
[0085] Color correction can improve the durability of the polyvinyl alcohol film. The color-correcting bath may contain more than 0wt% and 10wt% or less, preferably 1wt% to 5wt% potassium iodide. Within this range, the polarizer according to the present invention can be effectively implemented. For example, the amount of potassium iodide contained in the color correction bath may be 0.01wt%, 0.05wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt% or 10wt%.
[0086] The color correction bath may be set to a temperature of 20° C. to 50° C., specifically 20° C. to 40° C. In the color correction process, the polyvinyl alcohol film may be immersed in the color correction bath for 10 seconds to 120 seconds, specifically 10 seconds to 80 seconds. Within this range, the polarizer according to the present invention may be effectively implemented.
[0087] For example, the color correction bath can be set to 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, 31°C, 32°C, 33°C, 34°C, 35°C, 36°C, 37°C, 38°C, 39°C, 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C or 50°C. For example, in the color correction process, the polyvinyl alcohol film can be immersed in the color correction bath for 10 seconds, 15 seconds, 20 seconds, 25 seconds, 30 seconds, 35 seconds, 40 seconds, 45 seconds, 50 seconds, 55 seconds, 60 seconds, 65 seconds, 70 seconds, 75 seconds, 80 seconds, 85 seconds, 90 seconds, 95 seconds, 100 seconds, 105 seconds, 110 seconds, 115 seconds or 120 seconds.
[0088] After the color correction process, the temperature of the polyvinyl alcohol film may be 50° C. to 90° C., specifically 50° C. to 70° C. Within this range, the polarizer may have the surface roughness according to the present invention.
[0089] For example, after the color correction process, the temperature of the polyvinyl alcohol film may be 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C.
[0090] In one embodiment, the polarizer may include a hydrophobic polyvinyl alcohol resin and may be manufactured by the above-mentioned manufacturing process, thereby having substantially the same surface roughness on opposite surfaces thereof in a thickness direction of the polarizer. Therefore, even when the protective film is bonded to the opposite surface of the polarizer via the bonding layer, the polarizer may have a maximum metal ion penetration length of 400 μm or less on the opposite surface thereof.
[0091] For example, the difference in surface roughness Ra between the opposite surfaces of the polarizer may be 5 nm or less, eg, 0 nm to 5 nm, 0 nm to 3 nm.
[0092] For example, the difference in surface roughness Ra between the opposite surfaces of the polarizer may be 0 nm, 0.01 nm, 0.05 nm, 0.1 nm, 0.2 nm, 0.3 nm, 0.4 nm, 0.5 nm, 0.6 nm, 0.7 nm, 0.8 nm, 0.9 nm, 1 nm, 1.1 nm, 1.2 nm, 1.3 nm, 1.4 nm, 1.5 nm, 1.6 nm, 1.7 nm, 1.8 nm, 1.9 nm, 2.1 nm, 2.2 nm, 2.3 nm, 2.4 nm, 2.5 nm, 2.6 nm, 2.7 nm, 2.8 nm, 2.9 nm, 2.1 ... .2nm, 2.3nm, 2.4nm, 2.5nm, 2.6nm, 2.7nm, 2.8nm, 2.9nm, 3nm, 3.1nm, 3.2nm, 3.3nm, 3.4nm, 3.5nm, 3. 6nm, 3.7nm, 3.8nm, 3.9nm, 4nm, 4.1nm, 4.2nm, 4.3nm, 4.4nm, 4.5nm, 4.6nm, 4.7nm, 4.8nm, 4.9nm or 5nm.
[0093] In one embodiment, the polarizer may have a surface roughness Rz of 0 nm to 80 nm, for example 0 nm to 75 nm, on a surface thereof facing the protective film. Within this range, the polarizing plate may have a maximum metal ion permeation length of 400 μm or less.
[0094] For example, the surface roughness Rz of the polarizer on the surface facing the protective film can be 0nm, 0.01nm, 0.05nm, 0.1nm, 0.2nm, 0.3nm, 0.4nm, 0.5nm, 0.6nm, 0.7nm, 0.8nm, 0.9nm, 1nm, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm, 20nm, 21nm, 22nm, 23nm, 24nm, 25nm, 26nm, 27nm, 28nm, 29nm, 30nm, 31nm , 32nm, 33nm, 34nm, 35nm, 36nm, 37nm, 38nm, 39nm, 40nm, 41nm, 42nm, 43nm, 44nm, 45nm, 46nm, 47nm, 48nm, 49nm, 50nm, 51nm, 52nm, 53nm, 54nm, 55nm, 56nm, 57nm, 58nm, 59nm, 60nm, 61nm, 62nm, 63nm, 64nm, 65nm, 66nm, 67nm, 68nm, 69nm, 70nm, 71nm, 72nm, 73nm, 74nm, 75nm, 76nm, 77nm, 78nm, 79nm or 80nm.
[0095] In one embodiment, the surface roughness Rq of the polarizer on the surface facing the protective film can be 0nm to 20nm, for example 0nm to 15nm. Within this range, the polarizing plate can have a maximum metal ion penetration length of 400μm or less. For example, the surface roughness Rq of the polarizer on the surface facing the protective film can be 0nm, 0.01nm, 0.05nm, 0.1nm, 0.2nm, 0.3nm, 0.4nm, 0.5nm, 0.6nm, 0.7nm, 0.8nm, 0.9nm, 1nm, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm or 20nm.
[0096] The thickness of the polarizer 10 may be 12 μm or less. Within this range, the polarizing plate may have a reduced thickness. Preferably, the thickness of the polarizer is greater than 0 μm and 12 μm or less, more preferably greater than 0 μm and 10 μm or less. For example, the thickness of the polarizer can be 0.01μm, 0.05μm, 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, 10μm, 10.5μm, 11μm, 11.5μm or 12μm.
[0097] The first protective film 20 may be stacked on the upper surface of the polarizer 10 to protect the polarizer while improving the mechanical strength of the polarizing plate. The first protective film may include an optically transparent protective film.
[0098] The first protective film 20 can be formed by melt extruding an optically transparent resin. In some embodiments, the resin can be further subjected to a stretching process. The resin can include at least one selected from cellulose ester resins (including triacetyl cellulose, etc.), cyclic polyolefin resins (including cyclic olefin polymers (COP), etc.), polycarbonate resins, polyester resins (including polyethylene terephthalate (PET), etc.), polyether sulfone resins, polysulfone resins, polyamide resins, polyimide resins, non-cyclic polyolefin resins, polyacrylate resins (including poly (methyl methacrylate)), polyvinyl alcohol resins, polyvinyl chloride resins, polyvinylidene chloride resins, and acrylic resins.
[0099] Preferably, the first protective film may include at least one selected from cellulose ester resin, cyclic polyolefin resin, and polyester resin.
[0100] The thickness of the first protective film 20 may be 5 μm to 200 μm, specifically 5 μm to 100 μm, and more specifically 20 μm to 40 μm. Within this range, the first protective film may be used in the polarizing plate. For example, the thickness of the first protective film 20 may be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm, 26 μm, 27 μm, 28 μm, 29 μm, 30 μm, 31 μm, 32 μm, 33 μm, μm, 34μm, 35μm, 36μm, 37μm, 38μm, 39μm, 40μm, 41μm, 42μm, 43μm, 44μm, 45μm, 46μm, 47μm, 48μm m, 49μm, 50μm, 51μm, 52μm, 53μm, 54μm, 55μm, 56μm, 57μm, 58μm, 59μm, 60μm, 61μm, 62μm, 63μm, 64μm, 65μm, 66μm, 67μm, 68μm, 69μm, 70μm, 71μm, 72μm, 73μm, 74μm, 75μm, 76μm, 77μm, 78μm, 7 9μm, 80μm, 81μm, 82μm, 83μm, 84μm, 85μm, 86μm, 87μm, 88μm, 89μm, 90μm, 91μm, 92μm, 93μm, 94μm m, 95μm, 96μm, 97μm, 98μm, 99μm, 100μm, 105μm, 110μm, 115μm, 120μm, 125μm, 130μm, 135μm, 1 40μm, 145μm, 150μm, 155μm, 160μm, 165μm, 170μm, 175μm, 180μm, 185μm, 190μm, 195μm or 200μm.
[0101] The polarizing plate may further include a functional coating layer on the upper surface of the first protective film 20 , such as a hard coating layer, an anti-fingerprint layer, an anti-reflection layer, etc.
[0102] The second protective film 30 may be stacked on the lower surface of the polarizer to protect the polarizer while improving the mechanical strength of the polarizing plate. The second protective film 30 may include a film formed of the same or different kind of resin as the first protective film 20.
[0103] In one embodiment, when the first protective film is a cellulose ester resin film including triacetyl cellulose or the like, the second protective film may be a cellulose ester resin film including triacetyl cellulose or the like.
[0104] In another embodiment, when the first protective film is a polyester resin film including polyethylene terephthalate (PET) or the like, the second protective film may be a cyclic polyolefin resin including cyclic olefin polymer (COP) or a cellulose ester resin film including triacetyl cellulose or the like.
[0105] The second protective film 30 may have the same thickness as or a different thickness from that of the first protective film 20 .
[0106] In the polarizing plate, the first protective film 20 and the second protective film 30 may be bonded to the polarizer via a bonding layer. The bonding layer may be formed by a typical bonding agent for polarizing plates well known to those skilled in the art. For example, the bonding layer may be formed by a water-based bonding agent, a pressure-sensitive adhesive, a heat-curing adhesive, or a light-curing adhesive.
[0107] The water-based adhesive may include polyvinyl alcohol powder, a heat-curing crosslinking agent and water. The heat-curing crosslinking agent may include an aldehyde-based crosslinking agent such as formaldehyde, glyoxal, glutaraldehyde and glyoxylate, and a polyethylene imine-based crosslinking agent, but is not limited thereto.
[0108] The photocurable adhesive may include an epoxy-based compound (including alicyclic epoxy compounds), a (meth) acrylic compound (including hydroxyl-containing (meth) acrylates) and an initiator. The initiator may include at least one selected from a phosphorus-based photoradical initiator and a cationic photoinitiator (including an onium salt), preferably a mixture of a photoradical initiator and a cationic photoinitiator. The photocurable adhesive may also include typical additives such as antioxidants, pigments, etc.
[0109] Each adhesive layer may have a thickness of 0.01 μm to 10 μm, for example 0.01 μm to 1 μm, specifically 0.05 μm to 0.08 μm, or 1 μm to 10 μm, more specifically 2 μm to 3 μm. Within these thickness ranges, the adhesive layer may be used in an optical display device. For example, the thickness of each adhesive layer can be 0.01μm, 0.02μm, 0.03μm, 0.04μm, 0.05μm, 0.06μm, 0.07μm, 0.08μm, 0.09μm, 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm or 10μm.
[0110] although Figure 1 Not shown in the figure, the polarizing plate may further include an adhesive layer, such as a pressure-sensitive adhesive layer, on the lower surface of the second protective film 30 to stack the polarizing plate on the optical display panel.
[0111] Next, an optical display device according to one embodiment of the present invention will be described.
[0112] The optical display device according to an embodiment of the present invention may include a polarizer or a polarizing plate according to the present invention. The optical display device may include at least one of a liquid crystal display and a light emitting diode display. The light emitting display may include an organic / inorganic light emitting element as a light emitting element, such as a light emitting diode (LED), an organic light emitting diode (OLED), a quantum dot light emitting diode (QLED) and a light emitting material, such as a phosphor.
[0113] See also Figure 3 The liquid crystal display may include an embedded liquid crystal panel 100, a first polarizing plate 200 disposed on a light exiting surface of the embedded liquid crystal panel 100, and a second polarizing plate 300 disposed on a light incident surface of the embedded liquid crystal panel 100, wherein at least one of the first polarizing plate 200 and the second polarizing plate 300 may include a polarizing plate according to the present invention.
[0114] The embedded liquid crystal panel 100 may include a first substrate 110, a second substrate 120 arranged opposite the first substrate 110, a liquid crystal layer 130 arranged between the first substrate 110 and the second substrate 120, a touch sensor layer 140 arranged between the first substrate 110 and the liquid crystal layer 130, and a driving electrode and sensor layer 150 arranged between the liquid crystal layer 130 and the second substrate 120.
[0115] When one of the first polarizing plate 200 and the second polarizing plate 300 includes the polarizing plate according to the present invention, the other polarizing plate may include a typical polarizing plate well known to those skilled in the art.
[0116] although Figure 3 Although not shown in the figure, solid residues of the paste containing metal powder may remain in the first polarizing plate 200 and the in-cell liquid crystal panel 100. The paste containing metal powder is the same as described above.
[0117] Next, the present invention will be described in more detail with reference to some examples. However, it should be noted that these examples are provided for illustration only and should not be construed in any way as limiting the present invention.
[0118] Example 1
[0119] A polyvinyl alcohol film (VF-TS#2000, hydrophobic polyvinyl alcohol resin, thickness: 20 μm, Kuraray Co., Ltd.) washed with water at 25°C was subjected to swelling treatment in a 30°C water swelling bath.
[0120] After the swelling treatment, the film was immersed in a dye bath containing an aqueous solution of 1 mol / ml potassium iodide and 1 wt % boric acid at 30° C. for 65 seconds. Thereafter, the film was immersed in a crosslinking bath containing an aqueous solution of 2.5 wt % boric acid at 30° C. for 30 seconds.
[0121] After the cross-linking treatment, the film was stretched at 55° C. in a stretching bath filled with an aqueous solution containing 2.5 wt % of boric acid.
[0122] The polyvinyl alcohol film was stretched to a total elongation of 5.0 times or more of its initial length through washing, swelling, dyeing, crosslinking and stretching treatments. Then, the film was immersed in a color correction bath at 20° C. for 10 seconds, the color correction bath containing an aqueous color correction solution containing 3.5 wt % potassium iodide.
[0123] After the color correction treatment, the film was washed with water and dried at 60° C., thereby manufacturing a polarizer (thickness: 7 μm).
[0124] The surface roughness (Ra) of the polarizer was 1.1 nm and the difference in surface roughness Ra between the opposing surfaces thereof was 0 nm.
[0125] A triacetyl cellulose film having a hard coating layer is bonded to the upper surface of the polarizer via a water-based adhesive (prepared by dissolving polyvinyl alcohol resin powder in water while stirring the powder at 95°C, and then adding a thermosetting aldehyde cross-linking agent), and a triacetyl cellulose film is bonded to the lower surface of the polarizer via a water-based adhesive (prepared by dissolving polyvinyl alcohol resin powder in water while stirring the powder at 95°C, and then adding a thermosetting aldehyde cross-linking agent), thereby manufacturing a polarizing plate (the thickness of each adhesive layer is 50nm to 80nm).
[0126] Examples 2 to 4
[0127] A polarizer and a polarizing plate were manufactured in the same manner as in Example 1, except that the contents in each dyeing bath, crosslinking bath and stretching bath, and the boric acid concentration in the stretching bath, the stretching temperature and / or the drying temperature were changed as listed in Table 1.
[0128] Example 5
[0129] A photocurable adhesive was prepared, comprising: a (meth) acrylic compound including a hydroxyl-containing (meth) acrylate, an epoxy compound including an alicyclic epoxy resin, a cationic photoinitiator including an onium salt, and a phosphorus-based photoradical initiator. A polarizing plate was manufactured in the same manner as in Example 1 (the thickness of each adhesive layer was 2 μm to 3 μm), except that the prepared photocurable adhesive was used instead of the water-based adhesive.
[0130] Comparative Example 1
[0131] A polyvinyl alcohol film (VF-TS#3000, hydrophilic polyvinyl alcohol resin, thickness: 30 μm, Kuraray Co., Ltd.) washed with water at 25°C was subjected to swelling treatment in a water swelling bath at 30°C.
[0132] After the swelling treatment, the film was immersed in a dye bath filled with an aqueous solution containing 1 mol / ml potassium iodide and 1 wt% boric acid for 65 seconds at 30° C. Thereafter, the film was immersed in a cross-linking bath filled with an aqueous solution containing 2.5 wt% boric acid for 30 seconds at 30° C. After the cross-linking treatment, the film was stretched in a stretching bath filled with an aqueous solution containing 2.5 wt% boric acid at 50° C.
[0133] The polyvinyl alcohol film is stretched to a total elongation of 5.0 times or more of its original length through the washing treatment, the swelling treatment, the dyeing treatment, the cross-linking treatment and the stretching treatment.
[0134] Then, the film was immersed in a color correction bath filled with an aqueous solution for color correction containing 3.5 wt % potassium iodide at 20° C. for 10 seconds. After the color correction treatment, the film was washed with water and dried at 60° C., thereby manufacturing a polarizer (thickness: 12 μm).
[0135] A polarizing plate was produced in the same manner as in Example 1 using a polarizer.
[0136] Comparative Example 2
[0137] A polyvinyl alcohol film (VF-TS#2000, hydrophobic polyvinyl alcohol resin, thickness: 20 μm, Kuraray Co., Ltd.) washed with water at 25°C was subjected to swelling treatment in a water swelling bath at 30°C.
[0138] After the swelling treatment, the film was immersed in a dye bath containing an aqueous solution of 1 mol / ml potassium iodide and 1 wt % boric acid at 30° C. for 65 seconds. Thereafter, the film was immersed in a crosslinking bath containing an aqueous solution of 2.5 wt % boric acid at 30° C. for 30 seconds.
[0139] After the cross-linking treatment, the film was stretched at 50° C. in a stretching bath filled with an aqueous solution containing 3.5 wt % of boric acid.
[0140] The polyvinyl alcohol film was stretched to a total elongation of 5.0 times or more of its initial length through washing, swelling, dyeing and crosslinking treatments. Then, the film was immersed in a color correction bath containing an aqueous solution for color correction containing 3.5 wt % potassium iodide at 20° C. for 10 seconds.
[0141] After the color correction treatment, the film was washed with water and dried at 100° C., thereby manufacturing a polarizer (thickness: 7 μm).
[0142] A polarizing plate was produced in the same manner as in Example 1 using a polarizer.
[0143] Property evaluation
[0144] (1) Surface roughness of polarizer (unit: nm): The surface roughness Ra, Rz, and Rq of each polarizer were measured using a surface roughness tester (Park XE-100AFM, Park Systems, South Korea). In the non-contact mode of AFM (atomic force microscope), when a fine probe is placed near the sample surface, the three-dimensional shape of the sample can be obtained by measuring the interaction force between atoms. Using the probe placed near the polarizer surface, a surface roughness image was obtained within a measurement range of 1 μm x 1 μm, and data of 512 pixels in each of the X and Y directions was obtained at a scanning rate of 1 Hz.
[0145] (2) A sample was prepared by adhering a release film (PET film) having an adhesive layer to the upper surface of each polarizing plate manufactured in the examples and comparative examples. The prepared sample was adhered to a glass plate via a (meth) acrylic pressure-sensitive adhesive layer. 0.5 g of a silver powder-containing paste (containing 48 wt % of flaky silver powder with an average particle size (D50) of 5.0 μm, 10 wt % of a binder (cellulose acetate butyrate) and 42 wt % of a solvent (PGMEA) (SCPW-6, Electro-Lube Co., Ltd.)) was deposited on the polarizing plate to a thickness of 200 μm in the thickness direction thereof and placed at 60°C and 95% RH for 240 hours. The silver ion (Ag) between the polarizer and the polarizing plate protective film was measured using an optical microscope (ML61L, Olympus Co., Ltd.). + ) penetration length to obtain the maximum penetration length. The results are shown in Table 1 and Figure 4 middle.
[0146] Table 1
[0147]
[0148] As shown in Table 1, the polarizing plate according to the present invention can minimize the penetration of metal ions between the polarizer and the protective film. Therefore, after stacking a release film having an adhesive layer attached thereto on the polarizing plate, when the release film is removed from the polarizing plate, the polarizing plate according to the present invention can provide an effect of removing static electricity without affecting the polarizing function and luminous efficiency of the polarizing plate.
[0149] In contrast, the polarizing plates of Comparative Examples 1 and 2 had a maximum metal ion permeation length of more than 400 μm between the polarizer and the protective film, thereby failing to achieve the effects of the present invention.
[0150] from Figure 4 It can be seen that the maximum metal ion penetration length of the polarizing plate of Example 1 (corresponding to Figure 4 (B) in the figure is much smaller than the maximum metal ion penetration length of the polarizing plate in Comparative Example 1 (corresponding to Figure 4 (A) in the figure.
[0151] It should be understood that various modifications, changes, variations and equivalent embodiments may be made by those skilled in the art without departing from the spirit and scope of the present invention.
Claims
1. A polarizing plate comprising a polarizer and a protective film stacked on at least one surface of the polarizer, in, The polarizer includes a hydrophobic polyvinyl alcohol resin and has a surface roughness Ra of 10 nm or less on a surface thereof facing the protective film, When a paste containing metal powder is deposited on the surface of the polarizing plate in the thickness direction of the polarizing plate and left at 60° C. and 95% relative humidity for 240 hours, the polarizing plate has a maximum metal ion permeation length of 400 μm or less between the polarizer and the protective film.
2. The polarizing plate according to claim 1, wherein The polarizer has a surface roughness Rz of 0 nm to 80 nm on a surface thereof facing the protective film and a surface roughness Rq of 0 nm to 20 nm on a surface thereof facing the protective film.
3. The polarizing plate according to claim 1, wherein The polarizer has a difference in surface roughness Ra of 5 nm or less between opposing surfaces thereof.
4. The polarizing plate according to claim 1, wherein The hydrophobic polyvinyl alcohol resin comprises unsubstituted C1 to C 20 The hydrocarbon group serves as a hydrophobic functional group.
5. The polarizing plate according to claim 1, wherein The hydrophobic polyvinyl alcohol resin comprises a copolymer of a monomer mixture including at least one vinyl ester monomer and a monomer providing a hydrophobic functional group. The polarizing plate according to claim 5 , wherein: The monomers providing hydrophobic functional groups include C1 to C 20 A monomer containing a hydrocarbon repeating unit.
7. The polarizing plate according to claim 1, wherein The polarizer has a thickness of 12 μm or less.
8. The polarizing plate according to claim 1, wherein The protective film includes at least one selected from the following: cellulose ester resin, cyclic polyolefin resin, polycarbonate resin, polyester resin, polyethersulfone resin, polysulfone resin, polyamide resin, polyimide resin, non-cyclic polyolefin resin, polyacrylate resin, polyvinyl alcohol resin, polyvinyl chloride resin, polyvinylidene chloride resin and acrylic resin.
9. The polarizing plate according to claim 1, wherein The polarizer is bonded to the protective film via a bonding layer, and the bonding layer has a thickness of 0.01 μm to 10 μm. 10 . An optical display device comprising the polarizing plate according to claim 1 .
Citation Information
Patent Citations
Polarizer plate and optical display device comprising the same
KR1020130078606A
Reactor for incinerator with removal function of attachment
KR1020200099645A
Broadband polarizer made using ion exchangable fusion drawn glass sheets
CN105705969A
Display panel
CN107851409A
